(3fXGe GdeYdheGJ GdJShjbjI (B/s - (3TNGH, MajRIs ((3GdLRGFQ (B: s (3OGQ EjdjGA ddfTQ hGdJhRjY(B, s, 2024)
(3GdeaGgje GdGSGSjI Mhd fXGe GdeYdheGJ ,eGgjI fXGe GdeYdheGJ GdJShjbjI , echfGJ fXGe GdeYdheGJ GdJShjbjI , YfGUQg h feGPLg , GdHjFI GdJShSbjI GdeMjWI HfXGe GdeYdheGJ GdJShjbjI h GgejI h ahGFO h JUfjaGJ GdHjFI GdJShjbjI (B. s
(3GdeQGLY U(B.139s
Keywords: (3GdJShjbs